Sistem Jual Beli Kelapa Sawit oleh Peron CV Ibrahim Putra di Pangkalan Dewa Persfektif Ekonomi Syariah - Rahmad Kurniawan; Indah Dwi Ristiana Putri (Pusat Riset dan Inovasi Nasional, 2022)
The platforms are usually owned by individuals, in the village of Pangkalan Dewa, West Kotawaringin Regency, there are 5 palm oil platforms, one of which is the CV Ibrahim Putra platform. Many farmers sell their oil palm harvests to the CV Ibrahim Putra platform, this can be seen from the farmer data in 2021 that there are 200-250 permanent farmers who sell their oil palm harvests to the CV Ibrahim Putra platform. on the other platforms there are less than 100 farmers. This type of research is field research. Subjects consist of employees and farmers who sell their crops to the CV Ibrahim Putra platform. The technique of determining the subject is purposive sampling. The data analysis is data collection, data reduction, data presentation, and conclusion drawing and verification. The buying and selling system of the CV Ibrahim Putra platform is to pick up the fruit to the farmer's land or the farmer delivers it directly to the CV Ibrahim Putra platform, then the fruit is weighed using a ram scale, the fruit that has been weighed will be paid by the platform in cash with a receipt of the sale. The buying and selling system of the CV Ibrahim Putra platform in terms of transactions and pricing is legal according to Islam because there are no violations of Islamic sharia provisions. The presence of the CV Ibrahim Putra platform has a positive value for farmers and can improve the economic welfare of oil palm farmers.